2015
DOI: 10.1590/1678-4162-8113
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality and cut yield of pigs slaughtered over 100kg live weight

Abstract: Meat quality and cut yield of pigs slaughtered between 100 and 150kg live weight were evaluated. Pigs (417 Agroceres PIC barrows and gilts) were fed a daily allowance of 2.8kg per head from 80kg until 100.71±0.85, 118.58±0.99, 134.07±1.18 or 143.90±1.24kg live weight. Seventy-one pigs were used for the evaluation of primal and subprimal cuts. There was no interaction between sex and slaughter weight for any of the evaluated parameters. Ham, shoulder, and loin weights linearly increased (P<0.01; R²: 84.3-93.2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
(41 reference statements)
3
6
1
2
Order By: Relevance
“…Relatively few studies have been conducted evaluating the effects of HCW on fresh ham color outside of the few studies specific to the production of Parma hams. Similar to the findings of this study, Bertol et al (2015) found no relationship between slaughter weight and semimembranosus lightness, whereas redness linearly increased with HCW (β 1 = 0.1968). Chizzolini et al (1996) observed a moderate relationship between semimembranosus L* and HCW (r = −0.21), with heavy carcasses exhibiting darker ham color, but no relationship between HCW and semimembranosus redness was observed (Chizzolini et al, 1996).…”
Section: Discussionsupporting
confidence: 89%
“…Relatively few studies have been conducted evaluating the effects of HCW on fresh ham color outside of the few studies specific to the production of Parma hams. Similar to the findings of this study, Bertol et al (2015) found no relationship between slaughter weight and semimembranosus lightness, whereas redness linearly increased with HCW (β 1 = 0.1968). Chizzolini et al (1996) observed a moderate relationship between semimembranosus L* and HCW (r = −0.21), with heavy carcasses exhibiting darker ham color, but no relationship between HCW and semimembranosus redness was observed (Chizzolini et al, 1996).…”
Section: Discussionsupporting
confidence: 89%
“…In that study, pH of semimembranosus increased by 0.01 unit per 10 kg increase in marketing weight from 120 to 140 kg and decreased at a similar rate when marketing weight increased from 140 to 170 kg. In contrast, Piao et al (2004) and Bertol et al (2015) observed increases in ultimate pH at 0.02 and 0.01 respectfully per 10 kg marketing weight increase.…”
Section: Resultsmentioning
confidence: 72%
“…Other studies have reported similar data with chops from heavier carcasses being more tender. 17,18 This could be due to the current industry chilling practices in which carcasses are chilled as quickly as possible to prevent pale, soft, and exudative (PSE) meat quality defects. Compared to the larger, heavier carcasses which cool slower, smaller carcasses chill at a faster rate.…”
Section: Resultsmentioning
confidence: 99%